Gender-based violence in Papua New Guinea: An intervention to change knowledge, beliefs and behaviours - Karen O’Reilly; Jane L. Fowler (Global Public Health, 2025)
Gender-based violence (GBV) in Papua New Guinea has resulted in the country's recognition as one of the most dangerous places on the planet for women to live [Human Rights Watch. (2017). Papua New Guinea: Events of 2016. World Report. https://www.hrw.org/world-report/2017/country-chapters/papua-new-guinea] . This study explored the effectiveness of a training programme to change human service providers’ (HSPs) knowledge, beliefs and behaviour about GBV. Qualitative (written responses to questions) and quantitative (Social norms and beliefs about gender-based violence scale) data were collected pre- and post-training. HSPs showed increased understanding about the causes of GBV and ways of addressing this major health concern, and positive change in beliefs about and willingness to act on GBV, after training. This study has advanced research by formally evaluating GBV training in a non-Western, developing country. Results provide strong support for the effectiveness of such training. Suggestions for practice and future research are provided in the paper.